Ultrafast enzyme-responsive hydrogel for real-time assessment and treatment optimization in infected wounds - Yitao Zhao; Yong Tan; Chun Zeng; Weilun Pan (Journal of Nanobiotechnology)
Abstract Monitoring wound infection and providing appropriate treatment are crucial for achieving favorable outcomes. However, the time-consuming nature of laboratory culture tests may delay timely intervention. To tackle this challenge, a simple yet effective HDG hydrogel, composed of hydrogen peroxide (H₂O₂), dopamine, and GelMA polymer, is developed for the ultrafast detection and treatment of Staphylococcus aureus (SA) infections. The HDG hydrogel detects SA by exploiting its secreted catalase to catalyze H₂O₂, producing oxygen, which in turn accelerates the polymerization of colorless dopamine into deep brown polydopamine (PDA). The bacterial detection process takes only 10 min with high sensitivity, and the results can be readily recognized by the naked eye or quantified using a cell phone-based digital analysis. Moreover, the HDG hydrogel provides a dual antibacterial mechanism through chemical and photothermal therapies via the generated PDA, significantly improving bacterial clearance. In animal experiments, the HDG hydrogel demonstrated promising capabilities in monitoring and eliminating bacteria, enhancing collagen deposition, reducing inflammation, and promoting the healing of infected wounds. This multifunctional design offers an enzyme-responsive strategy for the rapid assessment and management of infections, simplifying infection evaluation and facilitating the development of advanced wound dressings. Graphical Abstract